STRATEGI KOMUNIKASI PEMASARAN MELALUI LIVE STREAMING TIKTOK DALAM MENINGKATKAN MINAT BELI KONSUMEN PADA BRAND LEODY - Fadia Lisa Radinka; Flora Meliana Siahaan (STKIP Subang, 2026)
The advancement of digital technology has transformed marketing communication patterns from conventional media into digital media, one of which is the live streaming feature on the TikTok platform. This feature allows business actors to interact directly with consumers in real-time; however, not all live streaming activities are able to provide an optimal impact on consumer purchase intention, thus requiring an in-depth study of the communication strategies applied. This study aims to identify and analyze the marketing communication strategy through TikTok live streaming in increasing consumer purchase intention at Brand Leody. The study employed a qualitative approach with a descriptive research type. Data were collected through participant observation of the @leody.id TikTok account, in-depth interviews with the host and consumers, and documentation, then analyzed using the Miles and Huberman model, comprising data reduction, data display, and conclusion drawing, with an analytical framework based on the concepts of interactive, educational, and persuasive communication. The results show that Brand Leody applies interactive communication through quick responses to comments and spontaneous question-and-answer sessions that build emotional closeness with consumers; educational communication through detailed product explanations, live demonstrations, and verifiable information transparency; and persuasive communication through a combination of authentic personal communication style, convincing product explanations, and exclusive promotional offers during live sessions. This study found that consumer trust built through authentic communication has an influence as strong as price incentives in driving purchase intention. It can be concluded that the integrated application of interactive, educational, and persuasive communication strategies through TikTok live streaming plays a significant role in building trust, closeness, and consumer purchase intention toward Brand Leody, and may serve as a reference for local fashion business actors in optimizing their digital marketing strategies.